UJI EFEKTIVITAS MACAM KAWAT PENGHANTAR LISTRIK SIPLO DAN PEMBERIAN PUPUK NPK TERHADAP PENINGKATAN KUALITAS HASIL TANAMAN PADI (Oryza sativa L.) VARIETAS PADJAJARAN - zainal abidin; Sugiarto Sugiarto; Indiyah Muwarni (AGRONISMA, 2022)
Rice plant (Oriza sativa L.) is a food plant that can produce rice as a staple food source for most of the Indonesian population. SIPLO application and the addition of NPK compound fertilizer can improve soil fertility and make it easier for plants to absorb nutrients in the soil. This study aims to determine the combination of SIPLO electric conductor type treatment and NPK compound fertilizer to increase productivity and quality of rice plants. The study was conducted from October 2021 to March 2022. The research method was carried out using a factorial RAK (Randomized Block Design) design with two factors. The first factor is the type of SIPLO electrical conducting wire, namely bendrat wire and enamel/copper wire. The second factor is NPK compound fertilizer consisting of 150 kg/ha, 300 kg/ha and 450 kg/ha. Each treatment combination was repeated three times. The results showed that there was an interaction with the treatment of SIPLO electrical conductors with the application of NPK compound fertilizer. The results showed a separate table for the treatment of SIPLO electrical conductor types with the application of NPK compound fertilizer. The weight of 1000 grains showed the optimum dose of 777.5 kg/ha resulting in a weight of 27.45 g. The yield of K2 shows a value of 84.90% and M2 is 84.93%. and Paddy tons per hectare separate table shows 10.05 tons/ha and M3 is 10.04 tons/ha. The treatment of enamel/copper wire + NPK compound fertilizer increased the productivity of rice plants by 92%.Keywords: Rice, Jawro, SIPLO, NPK compound fertilizer